2014
DOI: 10.1016/j.colsurfa.2012.10.049
|View full text |Cite
|
Sign up to set email alerts
|

The effects of molecular weight, evaporation rate and polymer concentration on pillar formation in drying poly(ethylene oxide) droplets

Abstract: Typically, when droplets of dilute suspensions are left to evaporate the final dry deposit is the familiar coffee-ring stain, with nearly all the solute deposited at the initial contact line. Contrastingly, in previous work we have shown that sessile droplets of poly(ethylene oxide) (PEO) solutions form tall central pillars (or monoliths) during a 4-stage drying process. We show that a dimensionless Péclet-type number P e, a ratio of the competing advective and diffusive motion of the dissolved polymer, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 26 publications
(35 reference statements)
4
36
0
Order By: Relevance
“…Even though we did not include the result of PEO solution, we observed similar Marangoni vortex for PEO, which was also observed in a previous study 31 . In fact, PEO has the same chemical structure as PEG but relatively large molecular weight (MW = 600,000, Sigma-Aldrich, USA).…”
Section: Discussionsupporting
confidence: 84%
“…Even though we did not include the result of PEO solution, we observed similar Marangoni vortex for PEO, which was also observed in a previous study 31 . In fact, PEO has the same chemical structure as PEG but relatively large molecular weight (MW = 600,000, Sigma-Aldrich, USA).…”
Section: Discussionsupporting
confidence: 84%
“…This behavior is reminiscent of the contraction stage seen in pillar formation in evaporating polymer droplets by Baldwin and Fairhurst (2014). 5.…”
Section: Creeping Salt Dropletsmentioning
confidence: 78%
“…They concluded that the drying behaviour of these droplets were defined by three critical factors; initial concentration, droplet geometry and evaporation rate. 29 In the latest work of Baldwin et al 30…”
Section: Besides Single Component Fluids and Colloidal Suspensions Dmentioning
confidence: 99%